A Revision of the Biostratigraphy and Strontium Isotope Dating of Oligocene-Miocene Outcrops in East Java, Indonesia - Essam F. Sharaf; Marcelle K. BouDagher-Fadel; J.A. (Toni) Simo; Alan R. Carroll (Ikatan Ahli Geologi Indonesia, 2014)
The biostratigraphic ranges of identified larger benthic and planktonic foraminifera from Tertiary exposures in East Java Basin have been tied to the ages constrained from the Strontium isotope dating of some of the most abundant large benthic foraminifera. Foraminiferal assemblages and Strontium data have provided precise age ranges of the different stratigraphic units. The age of the exposed Lower Kujung Formation is late Early Oligocene (Rupelian P20) to Late Oligocene ( Te1-4), equivalent to 28.78- 28.27 Ma). The age of the exposed Upper Kujung Formation is Late Oligocene, Chattian ( P22, Te1-4) to Early Miocene (Aquitanian, N5a, Te5), equivalent to 24.31- 23.44 Ma. The age of the exposed Tuban Formation is late Early Miocene, (Burdigalian) to Middle Miocene (Langhian, N5b-N9, Te5-Tf1), equivalent to 20.80- 15.25 Ma. The age of the exposed Ngrayong Formation is late Middle Miocene (Serravallian, N12-N13, Tf2), equivalent to 15.0- 13.0 Ma. Age boundaries between the lithostratigraphic units were determined as: Upper Kujung- Tuban (22 Ma), Tuban-Ngrayong (15.25 Ma) and Ngrayong -Bulu Member of the Wonocolo Formation (12.98 Ma).